2011
DOI: 10.1016/j.carbpol.2011.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and thermal properties of lignins from oil palm biomass as a substitute for phenol in a phenol formaldehyde resin production

Abstract: Lignins were extracted from oil palm empty fruit bunch after kraft and soda pulping process. The aim of this study was to characterise the chemical and thermal properties of these lignins as well as determine their suitability for partial incorporation into phenol formaldehyde resin. The analytical methods used were CHN analyser, FTIR spectroscopy, UV spectroscopy, TGA, DSC, GPC, 1H NMR and FESEM. The elemental analysis results showed that both lignins had similar contents of C, H and O. FTIR spectra also reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(47 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…This second stage began between 200 and 210 °C for the other samples. Different thermal decomposition stages observed for lignin with TGAs are in accordance with other literature reports (Domínguez et al 2008;González et al 2009;Ibrahim et al 2011;Hussin et al 2014).…”
Section: Thermal Propertiessupporting
confidence: 80%
See 2 more Smart Citations
“…This second stage began between 200 and 210 °C for the other samples. Different thermal decomposition stages observed for lignin with TGAs are in accordance with other literature reports (Domínguez et al 2008;González et al 2009;Ibrahim et al 2011;Hussin et al 2014).…”
Section: Thermal Propertiessupporting
confidence: 80%
“…1. These results (above 40%) revealed that the obtained soda lignins are stable at high temperature, which is attributed to the formation of highly condensed aromatic structures above 450 °C (Tejado et al 2007;Ibrahim et al 2011).…”
Section: Thermal Propertiesmentioning
confidence: 68%
See 1 more Smart Citation
“…As the global effort increases to find a high-valued biorefinery route, the importance of lignin quantity determination has proven to be paramount (Lupoi et al 2015). In pulping and paper-making, and the first generation cellulosic projects, most of the lignin is combusted (Mohamad Ibrahim et al 2011;Ragauskas et al 2014). The heterogenic complexity of the lignin provides a barrier to its fractionation and economical use for higher-valued purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Most lignin from the forest industry is either burned or directly disposed of in the form of liquid waste [14]. Lignin consists of functional groups exhibiting similar properties to phenol, therefore it is considered the most promising substitute for phenol targeting adhesive applications [15,16]. However, lignin is a large molecular weight polymer with a complex structure [17] which has low reactivity towards formaldehyde.…”
Section: Introductionmentioning
confidence: 99%